Pemosisian Desain Produk sebagai pendukung industri kerajinan: Tinjauan sudut pandang Pemerintah Indonesia tahun 1970-1980 - Azizah Syafira; Achmad Syarief (Institut Seni Indonesia Yogyakarta, 2023)
Product design education was officially established in 1973 by the Department of Art Education at ITB. In this era, product design is ideally conceived as a discipline directly connected to the manufacturing industry, with its graduates professing to be industrial designers. The designs are intended to be manufactured on a mass scale. However, at the time, the manufacturing industry in Indonesia was still dominated by small-to medium-scale craft-based industries. Therefore, the conventional comprehension of product design was not fully concurrent with the Indonesian economic situation between 1970 and 1980 if adopted out of context. On other hand, some phenomena implied the intention of the Indonesian government to posit product design discipline as a support for the development of the craft industry through the involvement of several activities, such as training and exhibitions. This situation depicts the gap in knowledge between what was understood as the basis of product design education and the government's agenda for establishing product design in Indonesia. This research uses a historical approach to investigate documents and other resources regarding establishing a Product Design major in ITB. The resources studied to determine the positioning of product design in Indonesia from the perspective of the government's economic agenda at the time, that are discussed in this paper.